التوافق الدراسي ومستوى النضج الانفعالي وعلاقتهما ببعض المتغيرات لدى عينة من طلبة جامعة دمشق - نعيسة رغداء علي (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
هدف البحث إلى: تعرف مستوى التوافق الدراسي ومستوى النضج الانفعالي لدى عينة من طلبة جامعة دمشق. تعرف العلاقة بينهما. تعرف دلالة الفروق في إجابات أفراد عينة البحث على مقياس التوافق الدراسي ومقياس النضج الانفعالي وفق متغيرات البحث: (نوع التخصص الجامعي، السنة الدراسية). واعتمدت الباحثة على المنهج الوصفي التحليلي، واستخدمت أداتي البحث: (مقياس التوافق الدراسي، ومقياس النضج الانفعالي). وشملت عينة البحث (400) طالباً وطالبةً من كليتي الاقتصاد والتربية في جامعة دمشق. ومن أهم النتائج التي توصل إليها البحث: 1) توجد علاقة ارتباطية إيجابية ذات دلالة إحصائية بين درجات الطلبة على مقياس التوافق الدراسي ودرجاتهم على مقياس النضج الانفعالي. 2) توجد فروق ذات دلالة إحصائية بين متوسطات درجات الطلبة على مقياس التوافق الدراسي وعلى مقياس النضج الانفعالي تُعزى إلى متغير التخصص الدراسي لصالح طلبة كلية الاقتصاد. 3) توجد فروق ذات دلالة إحصائية بين متوسطات درجات الطلبة على مقياس التوافق الدراسي وعلى مقياس النضج الانفعالي تُعزى إلى متغير السنة الدراسية لصالح طلبة السنة الرابعة. The aim of this study is: 1. know the level of stacademic compatibility and level of emotional maturity among a sample of students of Damascus University . 2 . know the relationship between them. 3. know the significance of differences in the studentts’ responses on a scale of cademic compatibility a and emotional maturity scale based on the variables of specialization school year. The researcher relied on descriptive analytical method, and used two tools: (scale academic compatibility and emotional maturity scale). The research sample included 400 students of the faculties of Economics and Education at Damascus University. Among the most important findings of the research are: There is a positive correlation statistically significant differences among students’ scores on an academic compatibility scale and their grades on a scale of emotional maturity. There are significant differences between the mean scores of the students on academic compatibility scale and emotional maturity scale attributed to the variable course of study for the benefit of students of the Faculty of Economy. There are significant differences among the mean scores of the students on academic compatibility scale and emotional maturit scale attributed to the variable of the school year for students of the fourth year.